Contrast and Assimilation Effects on Self-Evaluation of Performance and Task Interest in a Sample of Elementary School Children - Bosch, Jannis; Wilbert, Jürgen (Frontiers in Education, 2020)
Social comparison processes and the social position within a school class already play a major role in performance evaluation as early as in elementary school. The influence of contrast and assimilation effects on self-evaluation of performance as well as task interest has been widely researched in observational studies under the labels big-fish-little-pond and basking-in-reflected-glory effect. This study examined the influence of similar contrast and assimilation effects in an experimental paradigm. Fifth and sixth grade students (n = 230) completed a computer-based learning task during which they received social comparative feedback based on 2x2 experimentally manipulated feedback conditions: social position (high vs. low) and peer performance (high vs. low). Results show a more positive development of task interest and self-evaluation of performance in both the high social position and the high peer performance condition. When transferred to the school setting, results of this study suggest that students who already perform well in comparison to their peer group are also the ones profiting most from social comparative feedback, given that they are the ones who usually receive the corresponding positive performance feedback.